Using Facebook to Engage Iraqi EFL University Students in Learning - Gumar Karam, Hussein (Journal of College of Education, 2021)
Facebook was established in 2004 and has grown up increasable to become not only the most common social networking site in the world but also the most famous social networking tool of the past decade for students’ online learning. Traditional learning models concentrate on the one-way move of information from teacher to student in the shape of lecture and textbook; social application presents flexible space for personalization of learning and increased communication between teacher and student. In addition, the student can contribute with each other collaboratively and communicatively in the context of expanding activities and interactions that are unobstructed by place and time. This study attempt to find out the Iraqi University students' awareness of using Facebook in learning EFL. The sample who participated in the study were 150 students in the 2nd year at the Department of English, College of Education for Human Sciences/ Wasit University. Furthermore, results illustrated that students believe their language skills improved throughout using Facebook, and further, their confidence, motivation, manner relating to language learning and improved through their previous experiences. Facebook for learning and teaching because of its unique integrated function that offers pedagogical social. And technological.